A Mechanistic Insight into the Anti-Staphylococcal Mode of Action of (+)-Usnic Acid and Its Synergy with Norfloxacin Against Methicillin-Resistant Staphylococcus aureus - Bhavana Gangwar; Santosh Kumar; Parmanand Kumar; Anirban Pal; Mahendra P. Darokar (Biomolecules)
In this study, a global response analysis was performed to explore the mechanism of action of Usnic acid and its synergy with Norfloxacin, a well-known quinolone antibiotic to which MRSA clinical isolates showed resistance (MIC, 500 µg/mL). A microdilution assay, a growth kinetics analysis, a microscopic analysis, and cell-based assays consistently showed that Usnic acid possesses strong anti-staphylococcal activity (MIC, 7.8 µg/mL), causes cell leakage, modulates efflux pump activity, and synergizes with Norfloxacin against the multi-drug-resistant clinical isolate MRSA 2071. Whole-cell proteome profiling using gel-free proteomics-based nano-LC-ESI-QTOF-MS/MS revealed several proteins whose expression was significantly modulated by Usnic acid and Norfloxacin alone or in combination. Usnic acid downregulated the abundance of RNA polymerase subunits (RpoB and RpoC), carbamoyl phosphate synthase large subunit (PyrAB), chaperone (GroEL), and adenylosuccinate synthetase (PurA). Interestingly, proteins found to be upregulated in the presence of Usnic acid and Norfloxacin included oxidative-stress-related proteins such as peroxidase (Tpx), alkyl hydroperoxide reductase (AphC), and general stress protein (UspA). This study clearly shows that Usnic acid affects numerous cellular targets and can potentiate the action of Norfloxacin. Furthermore, an in vivo study showed that UA at low concentrations prevents body weight gain, but changes in other tested toxicological parameters were found to be within normal limits. Thus, UA at low doses appears to be a promising candidate for repurposing old antibiotics through combination therapy against MRSA infections.